Method for manufacturing electrode-integrated separator for lithium secondary battery

The described method addresses the challenges of adhesion and mass production in electrode-integrated separation membranes by using a carrier film and laminated pattern transfer, resulting in improved mechanical strength and reduced defects for lithium secondary batteries.

JP2025511523APending Publication Date: 2025-04-16LG CHEM LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2024554633
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-02-01
Filing Date
2024-01-19
Publication Date
2025-04-16

Smart Images

  • Figure 2025511523000001_ABST
    Figure 2025511523000001_ABST
Patent Text Reader

Abstract

The present invention relates to a method for manufacturing an electrode-integrated separator for a lithium secondary battery, and more particularly to a method for manufacturing an electrode-integrated separator for a lithium secondary battery, the method enabling mass production of the electrode-integrated separator more efficiently while minimizing the occurrence of defects.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application claims the benefit of priority based on Korean Patent Application No. 10-2023-0013551, dated February 1, 2023, and all contents disclosed in the documents of said Korean Patent Application are incorporated herein by reference.

[0002] The present invention relates to a method for producing an electrode-integrated separator for a lithium secondary battery. [Background technology]

[0003] The demand for secondary batteries to be used as driving power sources for mobile phones, laptops, tablet computers, mobile batteries, electric vehicles, personal mobility devices, etc. is steadily increasing along with the increasing functionality of these devices. In particular, lithium secondary batteries, which have a high operating voltage and a high energy density per unit weight, are the most widely used.

[0004] A lithium secondary battery generally has a structure in which a chargeable and dischargeable electrode assembly having a positive electrode, a separator, and a negative electrode is mounted in a battery case. The positive electrode and the negative electrode are manufactured by applying a slurry containing an electrode active material to one or both sides of a metal current collector, followed by drying and rolling.

[0005] The separator is one of the important factors that determine the life of a secondary battery and electrically insulates the positive and negative electrodes. The separator is required to have ion permeability and mechanical strength so that the electrolyte can pass through smoothly. As the range of applications of high-energy lithium secondary batteries expands, the demand for safety of the separator at high temperatures is also increasing.

[0006] Generally, a separator made of a substrate and an inorganic coating layer does not have sufficient adhesive strength with an electrode due to the material properties of the substrate, which causes partial lifting or wrinkles at the interface between the electrode and the separator. In addition, polyolefin, which is generally used as the substrate, has thermal stability problems such as melting at high temperatures.

[0007] To solve these problems, a method has been proposed in which the substrate is removed and a separator is formed only from an inorganic coating film. However, such separators still have insufficient adhesion to electrodes and extremely low insulation, making them vulnerable to internal short circuits when used in electrochemical devices. Such separators have fatal short circuits that occur inside the electrode assembly due to their low tensile strength and elongation rate, which can easily break the separator. In addition, non-uniformity in the separator coating and resulting defects can occur depending on the state of the electrodes (e.g., porosity and surface roughness).

[0008] Due to the poor mechanical properties of the separator and the difficulty in controlling defects, it has been difficult to mass-produce the electrode-integrated separator. Summary of the Invention [Problem to be solved by the invention]

[0009] The present invention provides a manufacturing method that enables mass production of electrode-integrated separators more efficiently while minimizing the occurrence of defects. [Means for solving the problem]

[0010] According to one embodiment of the invention, Providing a carrier film 100 having a release layer 102 formed thereon; forming a laminate pattern 150 including a porous layer pattern 104 and an adhesive layer pattern 106 laminated in sequence on a release layer 102 of the carrier film 100; forming an electrode active material layer pattern 203 on a metal substrate 200 for an electrode current collector; bonding the carrier film 100 and the metal substrate 200 for an electrode current collector such that the adhesive layer pattern 106 and the electrode active material layer pattern 203 are in contact with each other; transferring the porous layer pattern 104 and the adhesive layer pattern 106 onto the electrode active material layer pattern 203, and removing the carrier film 100 on which the release layer 102 is formed; The present invention provides a method for producing an electrode-integrated separator for a lithium secondary battery, comprising the steps of:

[0011] Hereinafter, the method for manufacturing the electrode-integrated separator for a lithium secondary battery according to an embodiment of the present invention will be described in more detail.

[0012] The terms and words used in this specification and the claims should not be interpreted in a limited manner to their ordinary or dictionary meanings, but should be interpreted in a manner that is consistent with the technical idea of ​​the invention, based on the principle that the inventor can appropriately define the concept of the term in order to best describe his / her invention.

[0013] In the present invention, when any one layer is bonded to another layer "through" another layer, it means that the one layer and the further layer are stacked and bonded together by the further layer interposed in at least a partial area between the one layer and the further layer.

[0014] As described in the Background of the Invention section, a separator made only of an inorganic coating film has a limitation in that it cannot be manufactured into a free-standing thin film due to its poor mechanical properties.

[0015] Due to these limitations, a method has been proposed in which an electrode-integrated separator is manufactured by coating an inorganic coating composition on an electrode. However, this method can cause non-uniformity in the separator coating and defects due to the electrode condition (e.g., porosity and surface roughness, etc.). Furthermore, this method has low productivity, making it difficult to mass-produce electrode-integrated separators.

[0016] As a result of the inventors' continued research, it was found that the following manufacturing method can be used to mass-produce electrode-integrated separators more efficiently while minimizing the occurrence of defects.

[0017] According to one embodiment of the invention, Providing a carrier film 100 having a release layer 102 formed thereon; forming a laminate pattern 150 including a porous layer pattern 104 and an adhesive layer pattern 106 laminated in sequence on a release layer 102 of the carrier film 100; forming an electrode active material layer pattern 203 on a metal substrate 200 for an electrode current collector; bonding the carrier film 100 and the metal substrate 200 for an electrode current collector such that the adhesive layer pattern 106 and the electrode active material layer pattern 203 are in contact with each other; transferring the porous layer pattern 104 and the adhesive layer pattern 106 onto the electrode active material layer pattern 203, and removing the carrier film 100 on which the release layer 102 is formed; The present invention provides a method for producing an electrode-integrated separator for a lithium secondary battery, comprising the steps of:

[0018] The manufacturing method is easy to mass-produce by stacking individual layers constituting the electrode-integrated separator in a pattern. For example, the porous layer pattern means that porous layer units having any shape are continuously arranged at regular intervals. The adhesive layer pattern is stacked in order on the porous layer pattern. By forming the pattern of the individual layers in this manner, a plurality of electrode-integrated separators can finally be provided.

[0019] In particular, by laminating and transferring the porous layer pattern onto the electrode active material layer pattern using the carrier film, it is possible to minimize the occurrence of defects such as breaks, tears, and wrinkles during the manufacturing process.

[0020] FIG. 5 is a plan view that illustrates a part of the steps included in the method for producing an electrode-integrated separator for a lithium secondary battery according to an embodiment of the invention.

[0021] 5, the manufacturing method may be performed by preparing a carrier film 100 on which the laminate pattern 150 is formed and a metal substrate 200 for an electrode current collector on which an electrode active material layer pattern 203 is formed, bonding the carrier film 100 and the metal substrate 200 for an electrode current collector together, and then removing the carrier film 100. Here, the configuration of each layer and the bonding method will be described in detail below.

[0022] According to one embodiment, the steps of providing a carrier film 100 having a release layer 102 formed thereon and forming a laminate pattern 150 including a porous layer pattern 104 and an adhesive layer pattern 106 sequentially laminated on the release layer 102 of the carrier film 100 are performed.

[0023] FIG. 1 is a cross-sectional view of a laminate pattern 150 including a porous layer pattern 104 and an adhesive layer pattern 106 formed on a carrier film 100 on which a release layer 102 is formed.

[0024] A transparent polymer substrate commonly used in the field of lithium secondary batteries can be used as the carrier film 100. As an example, the carrier film 100 may be a transparent film made of one or more polymer materials selected from the group consisting of high density polyethylene, low density polyethylene, linear low density polyethylene, ultra-high molecular weight polyethylene, polypropylene, polybutylene, polypentene, polyethylene terephthalate, polybutylene terephthalate, polyacetal, polyamide, polycarbonate, polyimide, polyether ether ketone, polyether sulfone, polyphenylene oxide, polyphenylene sulfide, and polyethylene naphthalene. The thickness of the carrier film 100 is not particularly limited and can be adjusted within a normal range in consideration of the efficiency of the manufacturing process.

[0025] The carrier film 100 used has a release layer 102 formed thereon. The release layer 102 may be formed on one surface or both surfaces of the carrier film 100.

[0026] The release layer 102 may be formed on the entire surface of one side of the carrier film 100. Alternatively, the release layer 102 may be formed in a pattern by continuously arranging two or more release layer units having any shape and size at regular intervals on one side of the carrier film 100.

[0027] A silicone-based release coating composition including a silicone-based resin, a silicone-based curing agent, and a thermal initiator can be used to form the release layer 102. Alternatively, a UV-curable coating composition including reactive compounds such as urethane acrylates, epoxy acrylates, polyester acrylates, and polyether acrylates can be used to form the release layer 102.

[0028] The release layer 102 is removed together with the carrier film 100 in the final stage. Therefore, the release layer 102 needs to have a surface energy that can exhibit an appropriate level of releasability. Preferably, the surface energy of the release layer 102 may be 15 dyn / cm to 30 dyn / cm, or 15 dyn / cm to 25 dyn / cm, or 16 dyn / cm to 25 dyn / cm, or 16 dyn / cm to 20 dyn / cm.

[0029] The thickness of the release layer 102 may be determined in the range of 1 μm to 200 μm, alternatively 2 μm to 100 μm, alternatively 2 μm to 50 μm, or alternatively 2 μm to 5 μm in order to exhibit appropriate release properties.

[0030] A porous layer pattern 104 and an adhesive layer pattern 106 are laminated in this order on the release layer 102 of the carrier film 100 to form a laminate pattern 150 .

[0031] The porous layer pattern 104 is formed by continuously arranging two or more porous layer units having any shape and size at regular intervals on the release layer 102. And the adhesive layer pattern 106 is formed by continuously arranging adhesive layer units on the porous layer units with the same shape, size and intervals as the porous layer units.

[0032] The porous layer pattern 104 and the adhesive layer pattern 106 may each be formed by a method such as coating, dispensing, transfer, printing, dipping, spraying, etc. As an example, the porous layer pattern 104 and the adhesive layer pattern 106 may each be formed using an apparatus such as a comma coater, a gravure printer, a micro gravure printer, and an offset printer.

[0033] The porous layer pattern 104 includes a polymer binder and inorganic fine particles dispersed on the polymer binder.

[0034] The polymer binder may be gelled when impregnated with a liquid electrolyte, and may exhibit a high degree of swelling. The electrolyte injected after assembly of the lithium secondary battery permeates the polymer binder, and the polymer binder that holds the absorbed electrolyte has electrolyte ion conducting ability. Therefore, the polymer binder may have a solubility index of 15 to 45 MPa. 1 / 2 The above polymers are preferably applicable.

[0035] As an example, the polymer binder may be one or more compounds selected from the group consisting of polyvinylidene fluoride, poly(vinylidene fluoride-hexafluoropropylene), poly(vinylidene fluoride-trichloroethylene), poly(vinylidene fluoride-chlorotrifluoroethylene), polymethyl methacrylate, polyacrylonitrile, polyvinylpyrrolidone, polyvinyl acetate, ethylene-vinyl acetate copolymer, polyethylene oxide, cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate, cyanoethyl pullulan, cyanoethylated polyvinyl alcohol, cyanoethyl cellulose, cyanoethyl sucrose, pullulan, carboxymethyl cellulose, acrylonitrile-styrene-butadiene copolymer, ethylene-propylene-diene terpolymer, sulfonated ethylene-propylene-diene terpolymer, styrene-butadiene rubber, fluororubber, and polyimide.

[0036] The inorganic fine particles form micropores due to empty spaces between particles, maintain their physical shape at high temperatures, and are electrochemically stable. The inorganic fine particles preferably do not undergo oxidation and / or reduction reactions in the operating voltage range of a secondary battery (e.g., 0 to 5 V on a Li / Li+ basis). The inorganic fine particles preferably have high electrolyte ion transfer ability. The inorganic fine particles preferably have as low a density as possible so that they can be well dispersed in the polymer binder. And, the inorganic fine particles preferably have a high dielectric constant so that they can contribute to increasing the degree of dissociation of the electrolyte salt in the electrolyte.

[0037] Preferably, the inorganic fine particles may be one or more types selected from the group consisting of inorganic particles having a dielectric constant of 1 or more, inorganic particles having piezoelectricity, and inorganic particles having lithium ion transport ability.

[0038] As an example, inorganic particles such as SrTiO3, SnO2, CeO2, MgO, NiO, CaO, ZnO, ZrO2, Y2O3, Al2O3, boehmite (AlO(OH)), Al(OH)3, TiO2, and SiC have a dielectric constant of 1 or more and are preferably applicable as the inorganic fine particles.

[0039] As another example, the inorganic particles having piezoelectricity are non-conductors at normal pressure, but when a certain pressure is applied, they become conductive due to a change in their internal structure. The piezoelectric inorganic particles have a high dielectric constant characteristic of 100 or more. In addition, when a certain pressure is applied to the piezoelectric inorganic particles to stretch or compress them, charges are generated, and one side is positively (+) charged and the other side is negatively (-) charged, generating a potential difference between the two sides. Due to the characteristics of the piezoelectric inorganic particles, when an internal short circuit occurs in the electrodes of the secondary battery due to an external impact, it is possible to prevent the positive electrode and the negative electrode from coming into direct contact, thereby achieving a gradual decrease in voltage and improved safety. Examples of the piezoelectric inorganic particles include BaTiO3, Pb(Zr,Ti)O3 (PZT), Pb 1-x La x Zr 1-y Ti y O3(PLZT), Pb(Mg 1 / 3 Nb 2 / 3 Inorganic particles such as PMN-PT, PbTiO3, and HfO2 are preferably applicable.

[0040] As another example, the inorganic particles having lithium ion transfer ability refer to inorganic particles that contain lithium elements and have the function of transferring lithium ions without storing lithium. The inorganic particles having lithium ion transfer ability can improve the lithium ion conductivity in the battery. Examples of such inorganic particles include Li3PO4, Li x Ti y (PO4)3(0 <x<2、0<y<3)、Li x Al y Ti z (PO4)3(0 <x<2、0<y<1、0<z<3)、(LiAlTiP) x O y(0 < x < 4, 0 < y < 13), Li x La y TiO3(0 < x < 2, 0 < y < 3), Li x Ge y P z S w (0 < x < 4, 0 < y < 1, 0 < z < 1, 0 < w < 5), Li x N y (0 < x < 4, 0 < y < 2), Li x Si y S z (0 < x < 3, 0 < y < 2, 0 < z < 4), and Li x P y S z Examples include inorganic particles such as (0 < x < 3, 0 < y < 3, 0 < z < 7).

[0041] Preferably, the inorganic fine particles are SrTiO3, SnO2, CeO2, MgO, NiO, CaO, ZnO, ZrO2, Y2O3, Al2O3, boehmite (AlO(OH)), Al(OH)3, TiO2, SiC, BaTiO3, Pb(Zr, Ti)O3, Pb 1-x La x Zr 1-y Ti y O3, Pb(Mg 1 / 3 Nb 2 / 3 )O3 - PbTiO3, HfO2, Li3PO4, Li x Ti y (PO4)3(0 < x < 2, 0 < y < 3), Li x Al y Ti z (PO4)3(0 < x < 2, 0 < y < 1, 0 < z < 3), (LiAlTiP) x O y (0 < x < 4, 0 < y < 13), Li x La y TiO3(0 < x < 2, 0 < y < 3), Li x Ge y P z S w (0 < x < 4, 0 < y < 1, 0 < z < 1, 0 < w < 5), Li x N y (0 < x < 4, 0 < y < 2), Li x Si y S z(0 < x < 3, 0 < y < 2, 0 < z < 4), and Li x P y S z It may be one or more selected from the group consisting of (0 < x < 3, 0 < y < 3, 0 < z < 7).

[0042] The inorganic fine particles preferably have a particle size of 0.001 μm to 10 μm. To ensure dispersibility in the porous layer pattern 104, the inorganic fine particles preferably have a particle size of 0.001 μm or more. However, when the particle size of the inorganic fine particles is excessively large, the thickness of the porous layer pattern 104 increases and the mechanical properties deteriorate, and internal short circuits may occur during charge and discharge of the lithium secondary battery due to the excessively large pore size. Therefore, the inorganic fine particles preferably have a particle size of 10 μm or less.

[0043] According to one embodiment, the porous layer pattern 104 can contain 10 to 99% by weight of the inorganic fine particles and 1 to 90% by weight of the polymer binder. To impart an appropriate porosity and insulation to the porous layer pattern 104, the inorganic fine particles are preferably contained in an amount of 10% by weight or more. However, when the inorganic fine particles are excessively contained, the mechanical properties of the porous layer pattern 104 may deteriorate due to weakening of the adhesive force. Therefore, the inorganic fine particles are preferably contained in an amount of 99% by weight or less.

[0044] According to one embodiment, the porous layer pattern 104 preferably has a porosity within an appropriate range for the manifestation of the characteristics of the porous layer. When the porosity of the porous layer is excessively large, internal short circuits may occur during charge and discharge of the lithium secondary battery. Therefore, the porosity of the porous layer pattern 104 is preferably 60% or less.

[0045] The thickness of the porous layer pattern 104 is preferably adjusted in the range of 5 μm to 100 μm, or 5 μm to 50 μm, or 10 μm to 50 μm for the manifestation of appropriate separator membrane performance.

[0046] The material of the adhesive layer pattern 106 is preferably electrochemically stable and has adhesive properties suitable for bonding the porous layer pattern 104 and the electrode active material layer pattern 203 .

[0047] Preferably, the adhesive layer pattern 106 can include one or more compounds selected from the group consisting of polyvinylidene fluoride, poly(vinylidene fluoride-hexafluoropropylene), poly(vinylidene fluoride-trichloroethylene), poly(vinylidene fluoride-chlorotrifluoroethylene), polymethyl methacrylate, polyacrylonitrile, polyvinylpyrrolidone, polyvinyl acetate, ethylene-vinyl acetate copolymer, polyethylene oxide, cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate, cyanoethyl pullulan, cyanoethylated polyvinyl alcohol, cyanoethyl cellulose, cyanoethyl sucrose, pullulan, carboxymethyl cellulose, acrylonitrile-styrene-butadiene copolymer, ethylene-propylene-diene terpolymer, sulfonated ethylene-propylene-diene terpolymer, styrene butadiene rubber, fluororubber, and polyimide.

[0048] The thickness of the adhesive layer pattern 106 is preferably adjusted in the range of 1 μm to 50 μm, alternatively 1 μm to 25 μm, or alternatively 2 μm to 25 μm, in order to achieve appropriate adhesiveness.

[0049] According to an embodiment, the carrier film 100 on which the release layer 102 is formed and the laminate pattern 150 are preferably transparent or semi-transparent, respectively. Here, transparent or semi-transparent means that light can pass through the carrier film 100 on which the release layer 102 is formed and the laminate pattern 150 without being optically scattered.

[0050] As a result, when the carrier film 100 on which the laminate pattern 150 is formed is superimposed on the metal substrate 200 for an electrode current collector on which the electrode active material layer pattern 203 is formed, the position of the electrode active material layer pattern 203 can be confirmed through the carrier film 100 on which the release layer 102 is formed and the laminate pattern 150. This will be described in more detail in the lamination process described later.

[0051] The transparency of the carrier film 100 on which the release layer 102 is formed and the laminate pattern 150 is not particularly limited numerically. The transparency is sufficient as long as the position of the electrode active material layer pattern 203 can be confirmed through the carrier film 100 and the laminate pattern 150.

[0052] Preferably, the carrier film 100 on which the release layer 102 is formed and the laminate pattern 150 can each have a light transmittance of 40% or more, or 40% to 80%, or 40% to 60%, or 45% to 55%, for visible light with a wavelength of 550 nm.

[0053] Taking into consideration the transparency of the carrier film 100 on which the release layer 102 is formed and the laminate pattern 150, it is preferable that the carrier film 100 on which the release layer 102 is formed, the porous layer pattern 104 and the adhesive layer pattern 106 each have a material and thickness selected within the above-mentioned range.

[0054] According to an embodiment, a step of forming an electrode active material layer pattern 203 on a metal substrate 200 for an electrode current collector is performed.

[0055] FIG. 2 is a cross-sectional view of a state in which an electrode active material layer pattern 203 is formed on a metal substrate 200 for an electrode current collector.

[0056] Materials known to have conductivity without inducing chemical changes in lithium secondary batteries can be used for the electrode current collector metal substrate 200. For example, the electrode current collector metal substrate 200 can be made of stainless steel, aluminum, copper, nickel, titanium, baked carbon, or aluminum or stainless steel that has been surface-treated with carbon, nickel, titanium, silver, or the like.

[0057] The metal substrate 200 for an electrode current collector may have a thickness of 3 μm to 500 μm. In order to increase the adhesive strength with the electrode active material layer pattern 203, the metal substrate 200 for an electrode current collector may have fine irregularities formed on its surface.

[0058] An electrode active material layer pattern 203 is formed on the metal substrate 200 for an electrode current collector.

[0059] The electrode active material layer pattern 203 is formed by continuously arranging at least two electrode active material layer units having any shape and size on the metal substrate 200 for an electrode current collector at a regular interval.

[0060] It is preferable that the electrode active material layer unit has the same shape and a smaller size than the porous layer unit described above in terms of ensuring the safety of the battery. As an example, as shown in Figures 3 and 5, it is preferable that the electrode active material layer pattern 203 has the same shape as the laminate pattern 150 and is large enough to be covered by the laminate pattern 150.

[0061] The electrode active material layer pattern 203 may be formed by a method such as coating, dispensing, transfer, printing, dipping, spraying, deposition, etc. As an example, the electrode active material layer pattern 203 may be formed by a patch coating method in which patch-type electrode active material layer units are arranged at regular intervals.

[0062] The electrode active material layer pattern 203 includes an electrode material that is a mixture of an electrode active material, a conductive material, and a binder. The electrode active material layer pattern 203 may have a thickness of 10 μm to 500 μm.

[0063] The conductive material can be used to provide electronic conductivity to the electrode. The conductive material can be used without any particular limitation as long as it has electronic conductivity without causing a chemical change in the lithium secondary battery. Non-limiting examples of the conductive material include carbon-based materials such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black, and carbon fibers; graphite such as natural graphite and artificial graphite; metal powder or metal fiber such as copper, nickel, aluminum, and silver; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; and conductive polymers such as polyphenylene derivatives.

[0064] The content of the conductive material can be adjusted within a range that does not induce a decrease in the capacity of the lithium secondary battery while exhibiting an appropriate level of conductivity. Preferably, the content of the conductive material may be 1 wt% to 10 wt%, or 1 wt% to 5 wt%, based on the total weight of the electrode material.

[0065] The binder is used to make the electrode material adhere well to the electrode current collector. For example, the binder may be polyvinyl alcohol, polyacrylate, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, a polymer containing ethylene oxide, polyvinylpyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylated styrene-butadiene rubber, epoxy resin, nylon resin, etc.

[0066] The content of the binder can be adjusted within a range that does not cause a decrease in the capacity of the lithium secondary battery while exhibiting an appropriate level of adhesiveness, and is preferably 1 wt % to 10 wt %, or 1 wt % to 5 wt %, based on the total weight of the electrode material.

[0067] When the electrode active material layer pattern 203 forms a positive electrode portion, any material capable of reversibly inserting and extracting lithium ions can be used as the electrode active material without any particular limitation.

[0068] As an example, the positive electrode active material may be a composite oxide or phosphate containing lithium and a metal selected from cobalt, manganese, nickel, iron, or a combination thereof.

[0069] When the electrode active material layer pattern 203 forms a negative electrode portion, the electrode active material may include a material capable of reversibly intercalating and deintercalating lithium ions, lithium metal, a lithium metal alloy, a material capable of doping and dedoping lithium, and a transition metal oxide.

[0070] According to an embodiment, the carrier film 100 and the metal substrate 200 for an electrode current collector are attached to each other such that the adhesive layer pattern 106 and the electrode active material layer pattern 203 are in contact with each other.

[0071] 3 and 5, the carrier film 100 and the metal substrate 200 for an electrode current collector are attached to each other such that the adhesive layer pattern 106 and the electrode active material layer pattern 203 are in contact with each other.

[0072] In order to ensure the efficiency of the lamination process, the carrier film 100 on which the release layer 102 is formed and the laminate pattern 150 are preferably transparent or semi-transparent. Here, transparent or semi-transparent means that light can pass through the carrier film 100 on which the release layer 102 is formed and the laminate pattern 150 without being optically scattered. Thus, when the carrier film 100 on which the laminate pattern 150 is formed is superimposed on the metal substrate 200 for an electrode current collector on which the electrode active material layer pattern 203 is formed, the position of the electrode active material layer pattern 203 can be confirmed through the carrier film 100 on which the release layer 102 is formed and the laminate pattern 150.

[0073] According to one embodiment, the bonding step may be performed by a method in which a carrier film 100 having two or more laminate patterns 150 including a porous layer pattern 104 and an adhesive layer pattern 106 formed on a release layer 102 and a metal substrate 200 for an electrode current collector having two or more electrode active material layer patterns 203 formed thereon are positioned such that the center of the adhesive layer unit constituting the adhesive layer pattern 106 coincides with the center of the electrode active material layer unit constituting the electrode active material layer pattern 203.

[0074] As an example, the lamination step may be performed using an align lamination device. Referring to Fig. 3, the lamination step may be performed by adjusting the positions of the carrier film 100 and the metal substrate 200 for an electrode current collector to a position where the center of each adhesive layer unit and the center of each electrode active material layer unit coincide with each other using the align lamination device, and then laminating them together. At this time, the aligning means of the align lamination device can check the position of the electrode active material layer pattern 203 through the carrier film 100 on which the release layer 102 is formed and the laminate pattern 150.

[0075] If necessary, before the lamination step, a step of confirming the lamination position of the electrode active material layer pattern 203, which is visually confirmed through the carrier film 100 on which the release layer 102 is formed and the laminate pattern 150, may be further performed.

[0076] Next, the porous layer pattern 104 and the adhesive layer pattern 106 are transferred onto the electrode active material layer pattern 203, and the carrier film 100 on which the release layer 102 is formed is removed.

[0077] The step of transferring the porous layer pattern 104 and the adhesive layer pattern 106 onto the electrode active material layer pattern 203 may be performed under heat and pressure. As an example, as shown in Fig. 3, the carrier film 100 and the metal substrate 200 for an electrode current collector are laminated together, and heat and pressure are applied to transfer the porous layer pattern 104 onto the electrode active material layer pattern 203 via the adhesive layer pattern 106. Preferably, the transfer step may be performed at a temperature of 80°C to 110°C and under a pressure of 10 kgf to 30 kgf.

[0078] FIG. 4 is a cross-sectional view of the state shown in FIG. 3 from which the release layer 102 and the carrier film 100 have been removed.

[0079] As explained above, in order for the release layer 102 to exhibit an appropriate level of releasability, it is preferable that the release layer 102 has a surface energy of 15 dyn / cm to 30 dyn / cm, or 15 dyn / cm to 25 dyn / cm, or 16 dyn / cm to 25 dyn / cm, or 16 dyn / cm to 20 dyn / cm.

[0080] By removing the release layer 102 and the carrier film 100, an electrode-integrated separator 500 for a lithium secondary battery is obtained, in which an electrode active material layer pattern 203, an adhesive layer pattern 106 and a porous layer pattern 104 are formed in sequence on the metal substrate 200 for an electrode current collector.

[0081] According to another embodiment of the present invention, a lithium secondary battery including an electrode-integrated separator 500 for a lithium secondary battery is provided.

[0082] The lithium secondary battery may include an electrode assembly including a counter electrode disposed on the porous layer pattern 104 of the electrode-integrated separator 500, an electrolyte impregnated in the electrode assembly, and a battery case that hermetically houses the electrode assembly and the electrolyte.

[0083] The lithium secondary battery includes the electrode assembly described above, and thus exhibits excellent durability and stable performance. The lithium secondary battery may have various shapes, such as a square shape, a cylindrical shape, and a pouch shape. The lithium secondary battery can be used as an energy supply source with improved performance and safety in the field of portable electronic devices, such as mobile phones, notebook computers, tablet computers, mobile batteries, and digital cameras; and in the field of transportation, such as electric cars, electric bikes, and personal mobility devices. Effect of the Invention

[0084] According to the present invention, a manufacturing method is provided that enables mass production of electrode-integrated separators more efficiently while minimizing the occurrence of defects. [Brief description of the drawings]

[0085] [Figure 1] 1 is a cross-sectional view of a laminate pattern 150 including a porous layer pattern 104 and an adhesive layer pattern 106 formed on a carrier film 100 on which a release layer 102 is formed. [Diagram 2] FIG. 2 is a cross-sectional view of a state in which an electrode active material layer pattern 203 is formed on a metal substrate 200 for an electrode current collector. [Diagram 3] 1 is a cross-sectional view of a state in which a carrier film 100 and a metal substrate 200 for an electrode current collector are bonded together so that an adhesive layer pattern 106 and an electrode active material layer pattern 203 are in contact with each other. [Figure 4]FIG. 4 is a cross-sectional view of a state in which the release layer 102 and the carrier film 100 have been removed from the state shown in FIG. 3. [Diagram 5] 1A to 1C are plan views each showing a schematic diagram of a part of steps included in a method for producing an electrode-integrated separator for a lithium secondary battery according to an embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0086] The functions and effects of the present invention will be described in more detail below through specific examples of the present invention. However, these are presented as examples for understanding the present invention. The following examples are not intended to limit the scope of the invention in any way, and it is obvious to those skilled in the art that various changes and modifications are possible within the scope of the scope and technical idea of ​​the present invention.

[0087] Example 1 <Material preparation> 1) A polyethylene terephthalate film (thickness: 125 μm) was prepared as the carrier film 100. A UV-curable coating composition containing urethane acrylate was prepared as the composition for forming the release layer 102.

[0088] 2) To prepare a composition for forming the porous layer pattern 104, inorganic fine particles AlO(OH) and a dispersant (BYK, DISPERBYK-111) were mixed in N-methyl-2-pyrrolidone (NMP) to prepare an inorganic fine particle dispersion with a solid content of 39%. The particle size (D60) of the inorganic fine particles measured with a particle size analyzer was 550 nm. A binder solution was prepared by dissolving 8 wt% of poly(vinylidene fluoride-co-hexafluoropropylene) and 6 wt% of a dispersant (BYK, DISPERBYK-111) in NMP. A homogenizer mixer was used to obtain a slurry in which the inorganic fine particle dispersion and the binder solution were uniformly mixed.

[0089] 3) As a composition for forming the adhesive layer pattern 106, a solution in which polyvinylidene fluoride was dissolved in NMP was prepared.

[0090] 4) A copper foil having a thickness of 10 μm was prepared as the metal substrate 200 for an electrode current collector.

[0091] 5) For forming the electrode active material layer pattern 203, an aqueous active material slurry was prepared that consisted of 95.1 wt % of active material consisting of 85 wt % of graphite active material, in which artificial graphite and natural graphite were mixed in a ratio of 4:6, and 15 wt % of SiO; 1.5 wt % of acetylene black as a conductive material; and 1.2 wt % of carboxymethyl cellulose (CMC) and 2.2 wt % of styrene butadiene rubber (SBR) as binders.

[0092] <Manufacturing electrode-integrated separator for lithium secondary batteries> The aqueous active material slurry was coated on a metal substrate 200 for an electrode current collector to form an electrode active material layer pattern 203. The electrode active material layer pattern 203 was formed by continuously arranging electrode active material layer units having a width of 60 mm, a length of 100 mm and a thickness of 85 μm at intervals of 20 mm.

[0093] Meanwhile, the composition for forming a release layer pattern was coated on a carrier film 100 to a thickness of 3 μm to form a release layer 102 having a surface energy of 16 dyn / cm. The composition for forming a porous layer pattern was printed on the release layer 102 to a thickness of 20 μm using a gravure printing device to form a porous layer pattern 104. The porous layer pattern 104 was formed by continuously arranging porous layer units having a width of 65 mm and a length of 105 mm at intervals of 10 mm. Next, the composition for forming an adhesive layer pattern was printed on the porous layer pattern 104 to a thickness of 4 μm using a gravure printing device to form an adhesive layer pattern 106.

[0094] The alignment means of the aligning lamination device was used to confirm the lamination position of the electrode active material layer pattern 203, which was visually confirmed through the carrier film 100 on which the release layer 102 was formed and the laminate pattern 150. The lamination position was adjusted so that the center of the adhesive layer unit and the center of the electrode active material layer unit coincided. Next, the aligning lamination device was used to laminate the carrier film 100 and the metal substrate 200 for electrode current collector so that the adhesive layer pattern 106 and the electrode active material layer pattern 203 were in contact with each other.

[0095] The laminate thus laminated was passed through a roll laminator at 95° C. and a pressure of 13 kgf, so that the porous layer pattern 104 and the adhesive layer pattern 106 were transferred onto the electrode active material layer pattern 203. Next, the carrier film 100 on which the release layer 102 was formed was removed to produce an electrode-integrated separator 500 for a lithium secondary battery.

[0096] Example 2 An electrode-integrated separator for a lithium secondary battery was prepared in the same manner as in Example 1, except that the composition of the UV-curable coating composition was changed to form a release layer 102 having a surface energy of 20 dyn / cm.

[0097] Comparative Example 1 The entire surface of an electrode current collector, which is a copper foil having a thickness of 10 μm, was coated with the same aqueous active material slurry as in Example 1 to form an electrode active material layer having a thickness of 85 μm. The same composition for forming a porous layer pattern as in Example 1 was coated on the electrode active material layer to form a porous layer having a thickness of 20 μm, thereby preparing an electrode-integrated separator for a lithium secondary battery.

[0098] Experimental Example (1) Surface energy of release layer (dyn / cm) Using a contact angle measuring device (DSA100 Drop Shape Analyzer, KRUSS Co.), drops of distilled water and diiodomethane were formed on the release layer 102, respectively, to measure the contact angle, and the surface energy of the release layer was calculated from the contact angle value.

[0099] (2) Light transmittance (%) Using a UV-VIS-NIR Spectrophotometer (SolidSpec-3700, SHIMADZU Co.), the total light transmittance of the carrier film 100 on which the release layer 102, the porous layer pattern 104 and the adhesive layer pattern 106 were formed in that order was measured, and the light transmittance value for visible light with a wavelength of 550 nm is shown in Table 1 below.

[0100] (3) Transfer and release properties The porous layer pattern 104 and the adhesive layer pattern 106 according to the above embodiment were transferred onto the electrode active material layer pattern 203, and the carrier film 100 on which the release layer 102 was formed was then removed. In the process, the transfer state and releasability were evaluated as good or bad, and are shown in Table 1 below.

[0101] (4) Appearance characteristics In the electrode-integrated separator for lithium secondary batteries according to the examples and comparative examples, the appearance of the porous layer pattern or the porous layer was evaluated as good or bad (pinholes were generated), and the results are shown in Table 1 below.

[0102] (5) Insulation properties In the electrode integrated separator for lithium secondary batteries according to the examples and comparative examples, the insulation resistance between the metal substrate for electrode current collector and the porous layer pattern or between the electrode current collector and the porous layer was measured and evaluated as good or bad (short circuit), and the results are shown in Table 1 below.

[0103] [Table 1]

[0104] Referring to Table 1, it was confirmed that the above-mentioned examples enable the efficient manufacture of an electrode-integrated separator for a lithium secondary battery while minimizing the occurrence of defects. [Explanation of symbols]

[0105] 100: Carrier film 102: Release layer 104: Porous layer pattern 106: Adhesive layer pattern 150: Laminated pattern 200: Metal substrate for electrode current collector 203: Electrode active material layer pattern 500: Electrode-integrated separator for lithium secondary batteries

Claims

1. providing a carrier film 100 having a release layer 102 formed thereon; forming a laminate pattern 150 including a porous layer pattern 104 and an adhesive layer pattern 106 sequentially laminated on a release layer 102 of the carrier film 100; forming an electrode active material layer pattern 203 on a metal substrate 200 for an electrode current collector; bonding the carrier film 100 and the metal substrate 200 for an electrode current collector such that the adhesive layer pattern 106 and the electrode active material layer pattern 203 are in contact with each other; transferring the porous layer pattern 104 and the adhesive layer pattern 106 onto the electrode active material layer pattern 203, and removing the carrier film 100 on which the release layer 102 is formed; The method for producing an electrode-integrated separator for a lithium secondary battery includes the steps of:

2. The bonding step includes: A carrier film 100 having two or more laminate patterns 150 including a porous layer pattern 104 and an adhesive layer pattern 106 formed on a release layer 102; The metal substrate 200 for an electrode current collector on which two or more electrode active material layer patterns 203 are formed is The bonding is carried out in a state in which the center of the adhesive layer unit constituting the adhesive layer pattern 106 and the center of the electrode active material layer unit constituting the electrode active material layer pattern 203 are aligned with each other. The method for producing the electrode-integrated separator for a lithium secondary battery according to claim 1 .

3. Before the lamination step, a lamination position of the electrode active material layer pattern 203 is visually confirmed through the carrier film 100 on which the release layer 102 is formed and the laminate pattern 150. The method for producing an electrode-integrated separator for a lithium secondary battery according to claim 1, further comprising:

4. 2. The method for manufacturing an electrode-integrated separator for a lithium secondary battery according to claim 1, wherein the carrier film (100) on which the release layer (102) is formed and the laminate pattern (150) each have a light transmittance of 40% or more for visible light having a wavelength of 550 nm.

5. 2. The method of claim 1, wherein the release layer has a surface energy of 15 dyn / cm to 30 dyn / cm.

6. 2. The method of claim 1, wherein the porous layer pattern (104) comprises a polymer binder and inorganic fine particles dispersed on the polymer binder.

7. 7. The method of claim 6, wherein the porous layer pattern (104) comprises 10 to 99 wt % of the inorganic fine particles and 1 to 90 wt % of the polymer binder.

8. The method for producing an electrode-integrated separator for a lithium secondary battery according to claim 6, wherein the polymer binder is one or more compounds selected from the group consisting of polyvinylidene fluoride, poly(vinylidene fluoride-hexafluoropropylene), poly(vinylidene fluoride-trichloroethylene), poly(vinylidene fluoride-chlorotrifluoroethylene), polymethyl methacrylate, polyacrylonitrile, polyvinylpyrrolidone, polyvinyl acetate, ethylene-vinyl acetate copolymer, polyethylene oxide, cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate, cyanoethyl pullulan, cyanoethylated polyvinyl alcohol, cyanoethyl cellulose, cyanoethyl sucrose, pullulan, carboxymethyl cellulose, acrylonitrile-styrene-butadiene copolymer, ethylene-propylene-diene terpolymer, sulfonated ethylene-propylene-diene terpolymer, styrene-butadiene rubber, fluororubber, and polyimide.

9. The inorganic fine particles are SrTiO 3 , SnO 2 , CeO 2 , MgO, NiO, CaO, ZnO, ZrO 2 , Y 2 O 3 , Al 2 O 3 , boehmite (AlO(OH)), Al(OH) 3 , TiO 2 , SiC, BaTiO 3 , Pb(Zr,Ti)O 3 , Pb 1-x La x Zr 1-y Ti y O 3 , Pb(Mg 1/3 Nb 2/3 )O 3 -PbTiO 3 , HfO 2 , Li 3 PO 4 , Li x Ti y (PO 4 ) 3 (0 < x < 2, 0 < y < 3), Li x Al y Ti z (PO 4 ) 3 (0 < x < 2, 0 < y < 1, 0 < z < 3), (LiAlTiP) x O y (0 < x < 4, 0 < y < 13), Li x La y TiO 3 (0 < x < 2, 0 < y < 3), Li x Ge y P z S w (0 < x < 4, 0 < y < 1, 0 < z < 1, 0 < w < 5), Li x N y (0 < x < 4, 0 < y < 2), Li x Si y S z (0 < x < 3, 0 < y < 2, 0 < z < 4), and Li x P y S z The method for producing an electrode-integrated separator for a lithium secondary battery according to claim 6, wherein x is at least one selected from the group consisting of (0<x<3, 0<y<3, 0<z<7).

10. 7. The method for manufacturing an electrode-integrated separator for a lithium secondary battery according to claim 6, wherein the inorganic fine particles have a particle size of 0.001 μm to 10 μm.

11. 2. The method of claim 1, wherein the adhesive layer pattern 106 comprises at least one compound selected from the group consisting of polyvinylidene fluoride, poly(vinylidene fluoride-hexafluoropropylene), poly(vinylidene fluoride-trichloroethylene), poly(vinylidene fluoride-chlorotrifluoroethylene), polymethyl methacrylate, polyacrylonitrile, polyvinylpyrrolidone, polyvinyl acetate, ethylene-vinyl acetate copolymer, polyethylene oxide, cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate, cyanoethyl pullulan, cyanoethylated polyvinyl alcohol, cyanoethyl cellulose, cyanoethyl sucrose, pullulan, carboxymethyl cellulose, acrylonitrile-styrene-butadiene copolymer, ethylene-propylene-diene terpolymer, sulfonated ethylene-propylene-diene terpolymer, styrene-butadiene rubber, fluororubber, and polyimide.

12. 2. The method of claim 1, wherein the step of transferring the porous layer pattern and the adhesive layer pattern onto the electrode active material layer pattern is performed under heat and pressure.

Citation Information

Patent Citations

  • Laminate for non-aqueous secondary battery

    JP2017103031A

  • Coating method of electrode for lithium secondary battery

    KR1020140028754A

  • Continuous lithium concentration system

    KR1020240034328A